(untitled) (Zurich, 2006)
There is a rich and historical relationship between theoretical physics and number theory. This volume presents a selection of problems which are currently in full development and inspire a lot of research going on.
Keywords: Number theory,Mathematical physics,Lý thuyết số học,Toán vật lý